2019
DOI: 10.1080/09546634.2019.1587145
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of guselkumab, administered with a novel patient-controlled injector (One-Press), for moderate-to-severe psoriasis: results from the phase 3 ORION study

Abstract: Objectives: Guselkumab, an interleukin-23 antagonist, is approved for self-administration with the UltraSafe Plus TM syringe to treat moderate-to-severe plaque-type psoriasis. We evaluated the efficacy, safety, pharmacokinetics, and acceptability of guselkumab administered using a novel patient-controlled injector (One-Press) in psoriasis patients. Materials and methods: This Phase 3, multicentre, double-blind, placebo-controlled study (ORION, Clinicaltrials.gov identifier-NCT02905331) randomized adults with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
0
47
0
3
Order By: Relevance
“…Thirty studies [32, 61, 62, 71, 73, 79, 84, 85, 9295, 97, 102105, 108, 109, 114118, 121, 123, 126128, 131], were excluded from the network in the sensitivity analysis which restricted trial inclusion to those that reported a minimum of 5% of patients with prior biologic exposure. Among these studies were all five studies [102105, 109] evaluating the lower dose of etanercept (50 mg weekly) and the only study evaluating DMF [131].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies [32, 61, 62, 71, 73, 79, 84, 85, 9295, 97, 102105, 108, 109, 114118, 121, 123, 126128, 131], were excluded from the network in the sensitivity analysis which restricted trial inclusion to those that reported a minimum of 5% of patients with prior biologic exposure. Among these studies were all five studies [102105, 109] evaluating the lower dose of etanercept (50 mg weekly) and the only study evaluating DMF [131].…”
Section: Resultsmentioning
confidence: 99%
“…A sensitivity analysis was carried out to test the effect of using 12-week rather than 16-week outcomes from three secukinumab trials (CLEAR [78], SIGNATURE [81] and CLARITY [82]). To test for small study bias, a further sensitivity analysis was carried out excluding the eighteen trials with fewer than 50 patients per trial arm [73, 84, 85, 100, 134147]. There were no major differences between the results of these sensitivity analyses and the base-case analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be preferred by individuals who experience injection‐site erythema, which is a common adverse event during etanercept treatment 107 . Moreover, auto‐injectors for guselkumab can help to improve patient adherence to self‐administration of subcutaneous injections with this potential stressful task 111 . Thus, studies show that IL‐23p19 inhibitors are a good therapeutic option in treating chronic plaque psoriasis, but the real test will be how these biologics perform in the real‐world clinical application.…”
Section: Biologicsmentioning
confidence: 99%
“…Various factors contribute to NIEs. The chemical and physical properties of biologics that may contribute to NIEs are summarized in Table 3 (Abbvie, 2018;Eshtiaghi & Gooderham, 2018;European Medicines Agency, 2005Ferris et al, 2019;Immunex Corporation, 2016;Kavanaugh et al, 2012;Lacour et al, 2017;Nakamura et al, 2017;Papp et al, 2016;Sator, 2018;Savage, Wittmann, Mcgonagle, & Helliwell, 2015;US Food and Drug Administration, 2008, 2011, 2017a, 2017c, 2017d, 2018a, 2018b, 2018c, 2019a, 2019bvan der Heijde et al, 2018).…”
Section: Types Of Negative Injection Experiencesmentioning
confidence: 99%